1994
DOI: 10.1210/en.135.5.1831
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent localization of thyroid hormone receptor isoforms in glial cells of rat brain

Abstract: The three currently recognized T3 binding thyroid hormone receptor (TR) isoforms, TR alpha 1, TR beta 1, and TR beta 2, arise from two distinct genes (alpha and beta), whereas two closely related non-T3-binding receptor variants, collectively designated TR alpha 2, arise from alternate splicing of the alpha gene transcript. Using a panel of specific antisera to these isoforms we have assessed the presence or absence of TRs in oligodendrocytes and astrocytes of rat cerebrum and cerebellum. Inferences as to colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…These findings seem to complement previously reported results that show a sig¬ nificant reduction of GFAP expression in the cerebellum and the hippocampal formation from neonatal hypothyroid rat brains (Faivre-Sarrailh et al 1991) and do not accord with the results reported by Munoz et al (1991) showing no effect on GFAP mRNA levels in hypothyroidism. All these data could indicate that astrocytes in separate areas of the brain respond in a distinctive fashion to alterations in thyroid state, as proposed by Carlson et al (1994).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These findings seem to complement previously reported results that show a sig¬ nificant reduction of GFAP expression in the cerebellum and the hippocampal formation from neonatal hypothyroid rat brains (Faivre-Sarrailh et al 1991) and do not accord with the results reported by Munoz et al (1991) showing no effect on GFAP mRNA levels in hypothyroidism. All these data could indicate that astrocytes in separate areas of the brain respond in a distinctive fashion to alterations in thyroid state, as proposed by Carlson et al (1994).…”
Section: Discussionsupporting
confidence: 57%
“…Thyroid honnone acts in astrocytes by binding to nuclear receptors (for review see Garcia-Segura et al 1996), which are expressed in the early stages of develop¬ ment and present a higher affinity for T3 at birth (cerebral hemisphere) or at day 14 (cerebellum) (Strait et al 1990, Puymirat 1992. Although expression of T3 nuclear receptors has been well characterized in neurones and oligodendrocytes, their presence in vivo in astrocytes has not yet been clarified (Carlson et al 1994, Bernal & Nunez 1995. However, Carlson et al (1996) have described the presence of thyroid hormone receptor isoforms by immunocytochemistry, as well as mRNA, to these recep¬ tors on cultured astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rodent thyroid gland begins to function after E17, while TH receptors (TRα/TRβ) are present from E14 and are expressed in OLGs and their precursors (Carlson et al, 1994;Barres et al, 1994). The ability of TH to trigger the effector mechanism that stops cell division and initiates differentiation becomes important around the time of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the contribution of these isoforms to related underlying states such as generalized arousal or trait anxiety that are important for goal-directed social behaviors (Churchland and Winkielman, 2012) has not been examined. Several lines of evidence, including the distribution of both TRα1 (Wallis et al, 2010)and TRβ (Carlson et al, 1994; Ercan-Fang et al, 1996)in the amygdala, the BNST, and hippocampus and the behavior of isoform specific knockout and transgenic mice, point to a role of TRs in the regulation of anxiety. In mice that lack TRα1, an increase in anxiety was seen in the open field test (Guadano-Ferraz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%